Application of Stream Conductivity to Activity of Potential Large-Scale Landslide - Tsai, Yuan Jung; Chen, Yi Jing; Weng, Chieh Hsuan; Syu, Fang Tsz; Hsu, Kun-An; Lee, Wei Lin (Frontiers in Earth Science, 2022)
Under climate changing, extreme rainfall event can cause catastrophic sediment-related disasters, such large-scale landslide. To disaster prevention work, the government has investigated the location of potential large-scale landslide by geological and geomorphological approach. However, the activity of potential large-scale landslide has to rely on expensive on-site monitoring system, for example, observed drill hole of groundwater and underground displacement. Recently, the variation of stream electronic conductivity has been proposed to investigate the activity of large-scale landslide in Japan. Therefore, this study applied this concept in Taiwan. Firstly, the temporal and spatial variation of stream electronic conductivity nearby the potential large-scale landslide have been survey. Accordingly, an interesting finding is that the spring water from the potential large-scale landslide can increase the concertation of chemical ion, and thus the value of stream electronic conductivity increase. Secondly, the comparison of rainfall data, stream electronic conductivity, and ground surface displacement has been analyzed. A sound agreement between with stream electronic conductivity and ground surface displacement. This result implied that the stream electronic conductivity could be a possible index to monitoring the activity of potential large-scale landslide indirectly.